Learning stability in economics with heterogeneous agents - Seppo Honkapohja; Kaushik Mitra (European Central Bank (ECB), 2002)
An economy exhibits structural heterogeneity when the forecasts of different agents have different effects on the determination of aggregate variables. We study how different forms of heterogeneity in structure, forecasts and adaptive learning rules affect the conditions for convergence of adaptive learning towards rational expectations equilibrium. Results are applied to the market model with supply lags, a New Keynesian model of interest rate setting and the monetary inflation model with heterogenous agents.
Keywords: D83; C62; E30; 330